PENINGKATAN HASIL BELAJAR TEMA 1 INDAHNYA KEBERSAMAAN MELALUI MODEL PEMBELAJARAN GROUP INVESTIGATION PADA SISWA KELAS 4 SDN 175 TANJAKAN - Eli Marlina (AKSELERASI: Jurnal Ilmiah Nasional, 2022)
This study aims to improve learning outcomes in theme 1 through the application of the Group Investigation learning model to 4th grade students at SDN 175 Tanjakan Bandung City. This research is Classroom Action Research (PTK) which is carried out in two cycles consisting of 4 stages, namely the planning, implementation, observation, and reflection stages. The subjects of this study were 4th grade students at SDN 175 Tanjakan, which consisted of 30 students. The data collection technique used was a test (observation, documentation) then the data was analyzed descriptively quantitatively. The results showed an increase in the average percentage of learning outcomes from cycle I totaling 18 students (60%) included in the complete classification, 12 students (40%) included in the incomplete classification classification and cycle II as many as 26 students (86.67%) entered into the complete classification and 4 students (13.33%) in the incomplete classification. Based on the results of the study, it can be concluded that the Group Investigation learning model can improve learning outcomes for theme 1 class 4 SDN 175 Tanjakan Bandung City.